2018
DOI: 10.1080/1369183x.2018.1454305
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of resource mobilisation among forced and voluntary return migrants in Mexico

Abstract: The rise in U.S. deportations has resulted in a growing number of studies focused on the reintegration experiences of these migrants in their home communities. Based on interviews with deportees shortly after their arrival home, these studies paint a picture of economic gloom, finding that deportees are too frequently stigmatized by governments and employers and consequently unemployed or working on the margins of their home economies. In contrast, our longitudinal and comparative study, which draws on the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…In the current era of immigration control, heterogeneous migrant statuses can limit migrants' opportunities to accumulate new resources and achieve their goals (de Haas et al, 2019;Hagan et al, 2019;Roberts et al, 2017). Undocumented status, which applies to many migrants working throughout North America and Europe (de Haas et al, 2019), generally leads to precarious and exploitative working conditions (De Genova & Peutz, 2010) and heightens the risk of unplanned expulsion (Cassarino, 2004;Roberts et al, 2017).…”
Section: Background (A) Migration Entrepreneurship and Economic Mobmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current era of immigration control, heterogeneous migrant statuses can limit migrants' opportunities to accumulate new resources and achieve their goals (de Haas et al, 2019;Hagan et al, 2019;Roberts et al, 2017). Undocumented status, which applies to many migrants working throughout North America and Europe (de Haas et al, 2019), generally leads to precarious and exploitative working conditions (De Genova & Peutz, 2010) and heightens the risk of unplanned expulsion (Cassarino, 2004;Roberts et al, 2017).…”
Section: Background (A) Migration Entrepreneurship and Economic Mobmentioning
confidence: 99%
“…Third, despite the limitations imposed by undocumented status, few studies of returnee entrepreneurship assess the impact of legal status abroad on labor market mobility following return. Two recent qualitative studies found that unplanned returns limit migrants' opportunities to marshal resources in preparation for labor market re-entry upon return (Gubert & Nordman, 2011;Hagan et al, 2019), and can push unprepared returnees into informal wage work or marginal self-employment as they struggle to find work in local labor markets (David, 2017;Mezger Kveder & Flahaux, 2012). In his study of occupational mobility, Lindstrom (2013) found that being undocumented in the United States was associated with higher odds of downward occupational mobility upon return, but was unrelated to self-employment.…”
Section: (B) Empirical Studies Of Self-employment Among Return Migrantsmentioning
confidence: 99%
“…While objective economic challenges such as debt and a lack of access to livelihood and labour opportunities are clearly obstacles to reintegration, a range of subjective, psychosocial challenges (feelings of loneliness, stigma, not being understood by loved ones and not fulfilling family expectations or responsibilities) can be just as important. Feelings of underachievement, shame and failure abound in the testimonies of returnees across multiple geographical settings (Hagan et al, 2019 ; Oeppen, 2013 ; Schuster & Majidi, 2015 ; Vathi & King, 2017 ). When this is added to traumatic migratory experiences and, for some, mistreatment by border authorities and detention (e.g.…”
Section: Recognising the Challenges Of Reintegration Processes And Pr...mentioning
confidence: 99%
“…As a result, in 2010, there were over 569,000 US-born minors in Mexican schools (Jacobo Suárez, 2014; Kline, 2013). This reverse migration trend has given rise to an increased interest in postdeportation experiences (Hagan, Wassink, & Castro, 2018), which have consistently remained ignored in the past.…”
Section: A Reverse Migration Trendmentioning
confidence: 99%